Carbamazepine-Fumaric Acid Co-Crystal Screening Using Solution Based Method - Syarifah, Abd Rahim; Chou, C. Tan; Noor Ashila, Ramle (EDP Sciences, 2015, 2016)
Co-crystals is a multi-component system which connected by non-covalent interactions, present physically as a solid form under ambient conditions. Nowadays, co-crystal has becoming as an alternative approach to improve the bioavailability of poor water soluble drugs especially for a weakly ionisable groups or neutral compounds. In this study the co-crystal screening was carried out for carbamazepine (CBZ) and fumaric acid (FUM) co-crystal former (CCF) using non-stoichiometric method (addition of CBZ to CCF saturated solution) and stoichiometric method (evaporation of 1:1 molar ratio of CBZ to CCF) in acetonitrile, ethyl acetate, propanol, ethanol and formic acid solvent systems. The crystals produced from the screening were characterized using Powder X-ray Diffraction (PXRD), Differential Scanning Calorimetry (DSC) and Fourier Transform Infrared (FT-IR). The PXRD analysis had confirmed that the co-crystal was successfully formed in both methods for all of the solvent system studied with an exception to formic acid in the stoichiometric method where no crystal was found precipitate. The findings from this study revealed that Form A and Form B of CBZ-FUM co-crystal had been successfully formed from different solvent systems.